In pursuit of an accurate spatial and temporal model of biomolecules at the atomistic level: a perspective on computer simulation. (1st January 2015) - Gray, Alan; Harlen, Oliver G.; Harris, Sarah A.; Khalid, Syma; Leung, Yuk Ming; Lonsdale, Richard; Mulholland, Adrian J.; Pearson, Arwen R.; Read, Daniel J.; Richardson, Robin A.
<x xml:space="preserve">Abstract</x> Despite huge advances in the computational techniques available for simulating biomolecules at the quantum‐mechanical, atomistic and coarse‐grained levels, there is still a widespread perception amongst the experimental community that these calculations are highly specialist and are not generally applicable by researchers outside the theoretical community. In this article, the successes and limitations of biomolecular simulation and the further developments that are likely in the near future are discussed. A brief overview is also provided of the experimental biophysical methods that are commonly used to probe biomolecular structure and dynamics, and the accuracy of the information that can be obtained from each is compared with that from modelling. It is concluded that progress towards an accurate spatial and temporal model of biomacromolecules requires a combination of all of these biophysical techniques, both experimental and computational.